Implementation of Small Group Discussion Online on Undergraduate Nursing Program Students of STIKes Dharma Husada Bandung - Erawan, Annisa Nur; Basar, Dira Salsabilla (LPPM STIKes Muhammadiyah Ciamis, 2023)
The COVID-19 pandemic in Indonesia has made the Ministry of Education and Culture modify all learning methods and systems to be implemented online, one of which is Small Group Discussion (SGD). The impact felt is that students do not understand the material because of the decrease in the intensity of learning meetings. In line with this phenomenon, this study aims to determine the level of effectiveness and learning evaluation materials based on attendance, activeness and learning achievement. This research design uses a questionnaire sheet, in the form of exploratory descriptive research with direct survey quantitative methods. The results of research to 155 respondents in the form of univariate data obtained as many as 69.03% of students in general stated that it was effective with the effectiveness of the attendance subvariable 87.7%, the effectiveness of the activeness subvariable 67.7% and the effectiveness of the learning achievement subvariable 47.09%. Thus it can be concluded that the implementation of this online SGD is effective. However, there is still a need to improve the supporting components in the form of a more attractive and modified learning system and environment in order to create a more effective SGD implementation.